A Cost-Benefit Analysis of a State-Funded Healthy Homes Program for Residents With Asthma: Findings From the New York State Healthy Neighborhoods Program. Issue 2 (March 2017) - Gomez, Marta; Reddy, Amanda L.; Dixon, Sherry L.; Wilson, Jonathan; Jacobs, David E.
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Context: Despite considerable evidence that the economic and other benefits of asthma home visits far exceed their cost, few health care payers reimburse or provide coverage for these services. Objective: To evaluate the cost and savings of the asthma intervention of a state-funded healthy homes program. Design: Pre- versus postintervention comparisons of asthma outcomes for visits conducted during 2008-2012. Setting: The New York State Healthy Neighborhoods Program operates in select communities with a higher burden of housing-related illness and associated risk factors. Participants: One thousand households with 550 children and 731 adults with active asthma; 791 households with 448 children and 551 adults with asthma events in the previous year. Intervention: The program provides home environmental assessments and low-cost interventions to address asthma trigger–promoting conditions and asthma self-management. Conditions are reassessed 3 to 6 months after the initial visit. Main Outcome Measures: Program costs and estimated benefits from changes in asthma medication use, visits to the doctor for asthma, emergency department visits, and hospitalizations over a 12-month follow-up period. Results: For the asthma event group, the per person savings for all medical encounters and medications filled was 1083 per in-home asthma visit, and the average cost of the visit was 302, for a benefit to program cost ratio of 3.58 and net benefit of 781 per asthma visit. For the active asthma group, per person savings was 613 per asthma visit, with a benefit to program cost ratio of 2.03 and net benefit of 311. Conclusion: Low-intensity, home-based, environmental interventions for people with asthma decrease the cost of health care utilization. Greater reductions are realized when services are targeted toward people with more poorly controlled asthma. While low-intensity approaches may produce more modest benefits, they may also be more feasible to implement on a large scale. Health care payers, and public payers in particular, should consider expanding coverage, at least for patients with poorly controlled asthma or who may be at risk for poor asthma control, to include services that address triggers in the home environment.